LANSKAP SPIRITUAL SITUS LIYANGAN - Daud Aris Tanudirjo; J.S.E. Yuwono; Ari Mukti Wardoyo Adi (BRIN, 2019)
Abstract Liyangan archaeological site in the village of Purbasari, Residency Temanggung, Central Java, is an Old Mataram settlement predictably existed from around 8th to 10th century CE. In this site, which was buried by thick layers of pyroclastic materials of Gunung Sindoro eruption, various artefacts as well as stone structures are found including pavement, altars, retaining walls, water-temple, and remains of wooden structures. One of the most interesting aspect of this site is the orientation of the stone structures. Although the whole settlement was arranged to follow the sloping contour of the Mount Sindoro, most of the stone structures were oriented to southeast, which was not common for stone shrines built at the same period. This paper attempts to explain the reason for such an exceptional orientation using landscape archaeological approach. Our research demonstrates that the ten Liyangan stone structures were oriented to either Mount Merapi, Baka Hill, or the Prambanan temple. The orientation of the stone structures is believed as a reflection of the spatial map and the cosmology of the community lived in Liyangan centuries ago. It is suggested here that such an orientation represents the so-called â€œspiritual landscapeâ€of the people.